Electrophilic Agonists Modulate the Transient Receptor Potential Ankyrin-1 Channels Mediated by Insulin and Glucagon-like Peptide-1 Secretion for Glucose Homeostasis - Marisa Jadna Silva Frederico; Andreza Cipriani; Jocelyn Brice Alexandre Heim; Ana Karla Bittencourt Mendes; Marcela Aragón; Joana Margarida Gaspar; Nylane Maria Nunes De Alencar; Fátima Regina Mena Barreto Silva (MDPI AG, 2023)
This pre-clinical study investigated the transient receptor potential ankyrin-1 (TRPA1) channels on modulating targets for glucose homeostasis using agonists: the electrophilic agonists, cinnamaldehyde (CIN) and allyl isothiocyanate (AITC), and the non-electrophilic agonist, carvacrol (CRV). A glucose tolerance test was performed on rats. CIN and AITC (5, 10 and 20 mg/kg) or CRV (25, 100, 300, and 600 mg/kg) were administered intraperitoneally (i.p.), and glycemia was measured. In the intestine, Glucagon-like peptide-1 (GLP-1) and disaccharidase activity were evaluated (in vivo and in vitro, respectively). Furthermore, in vivo and in vitro insulin secretion was determined. Islets were used to measure insulin secretion and calcium influx. CIN and AITC improved glucose tolerance and increased insulin secretion in vivo and in vitro. CRV was unable to reduce glycemia. Electrophilic agonists, CIN and AITC, inhibited disaccharidases and acted as secretagogues in the intestine by inducing GLP-1 release in vivo and in vitro and contributed to insulin secretion and glycemia. The effect of CIN on calcium influx in pancreatic islets (insulin secretion) involves voltage-dependent calcium channels and calcium from stores. TRPA1 triggers calcium influx and potentiates intracellular calcium release to induce insulin secretion, suggesting that electrophilic agonists mediate this signaling transduction for the control of glycemia.